2015
DOI: 10.1177/1059840515605508
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Literature on Culturally Adapted Obesity Prevention Interventions for African American Youth

Abstract: Obesity and overweight prevalence in African American (AA) youth continues to be one of the highest of all major ethnic groups, which has led researchers to pursue culturally based approaches as a means to improve obesity prevention interventions. The purpose of this systematic review was to evaluate culturally adapted obesity prevention interventions targeting AA youth. A search of electronic databases, limited to multicomponent culturally adapted obesity prevention controlled trials from 2003 to 2013, was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…Previous research has shown that the availability of school nurses is essential in health promotion and the support of well-being for schoolchildren (Larsson, Bj€ ork, Ekebergh, & Sundler, 2013;Thorstensson, Fr€ oden, Vikstr€ om, & Andersson, 2015). However, to strengthen the school nurses' knowledge in this area, it may be useful to work in teams with the parents (Lofton, Julion, McNaughton, Bergren, & Keim, 2016) and the dieticians (Melin & Lenner, 2009). Furthermore, Tucker and Lanningham-Foster (2015) show that children who were overweight can feel supported when health messages are delivered in a creative way in the classroom and when health promotion nursing is integrated into existing structures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the availability of school nurses is essential in health promotion and the support of well-being for schoolchildren (Larsson, Bj€ ork, Ekebergh, & Sundler, 2013;Thorstensson, Fr€ oden, Vikstr€ om, & Andersson, 2015). However, to strengthen the school nurses' knowledge in this area, it may be useful to work in teams with the parents (Lofton, Julion, McNaughton, Bergren, & Keim, 2016) and the dieticians (Melin & Lenner, 2009). Furthermore, Tucker and Lanningham-Foster (2015) show that children who were overweight can feel supported when health messages are delivered in a creative way in the classroom and when health promotion nursing is integrated into existing structures.…”
Section: Discussionmentioning
confidence: 99%
“…85 There are very few pilot or feasibility studies that have evaluated the process of culturally adapting lifestyle intervention programmes in the UK, with the majority completed in the USA with Latino, Hispanic and African-American minority communities. [86][87][88] Findings from these studies are not wholly applicable to populations living in the UK. In addition, Sidhu et al 89 found that cultural adaptations to lay-led, group-based lifestyle interventions were inconclusive with regard to increased effectiveness, although structural adaptations were successful in increasing attendance, albeit mostly among women.…”
Section: Discussionmentioning
confidence: 87%
“…[33][34][35][36][37][38] rationale Very few systematic reviews have looked at site or setting for engaging African Americans in health promotion, primarily focusing on 'cultural adaptions' of evidencebased interventions. [39][40][41][42][43] Of those that have, they were largely focused on recruitment strategies of participants for clinical trials from sites that include churches, barbershops and hair salons. 44 45 One synthesis of the literature examined interventions delivered in barbershops and hair salons but did not focus on African Americans as the target population.…”
Section: Introductionmentioning
confidence: 99%